Penggunaan Bahasa Gaul Anak Remaja Jakarta Selatan; Suatu Kajian Semantik - Karlya, Aisy (UIR PRESS, 2022)
Actually slang itself has existed for a long time, but the mention of the language designation is different. In the past, slang was better known as prokem language. This prochem language was popular in the 1980s. Initially, slang was only used by certain groups. It is only used by certain groups because the initial purpose of this language is so that only members of that group will recognize its meaning. Each group has their own distinctive characteristics of slang. So that people who are not members of the group do not recognize the meaning of the language they use in speaking. This South Jakarta language research uses descriptive qualitative methods. Qualitative method is research that intends to understand the phenomenon of what is experienced by research subjects (Moleong, 2004: 6). And also the data collection technique in this study used the listen and note method because it was in the form of writing. The listening method is a data acquisition that is done by listening to a language use (Mahsun, 2005: 90). Listen and record is a process that is documented by recording the data that has been collected. Researchers have found 23 languages ​​that were taken from interviewing sources from Jakarta and some of the data was taken from social media such as Instagram, tiktok, whatsapp, based on the results of the above discussion as a whole what was studied there was the use of language that was reversed or not in accordance with the KBBI and PUEBI.